Hypercholesterolemia is associated with hyperactive cardiac mTORC1 and mTORC2 signaling - Glazer, Hilary P. (2009)
Nutritional excess and hyperlipidemia increase the heart’s susceptibility to ischemic injury. Mammalian target of rapamycin (mTOR) controls the cellular response to nutritional status and may play a role in ischemic injury. To explore the effect of hypercholesterolemia on cardiac mTOR signaling, we assessed mTOR signaling in hypercholesterolemic swine (HC) that are also susceptible to increased cardiac ischemia-reperfusion injury. Yucatan pigs were fed a high-fat/high-cholesterol diet for 4 weeks to induce hypercholesterolemia, and mTOR signaling was measured by immunoblotting and immunofluorescence in the non-ischemic left ventricular area. Total myocardial mTOR and raptor levels were markedly increased in the HC group compared to the normocholesterolemic group, and directly correlated with serum cholesterol levels. mTOR exhibited intense perinuclear staining in myocytes only in the HC group. Hypercholesterolemia was associated with hyperactive signaling upstream and downstream of both mTOR complexes, including myocardial Akt, S6K1, 4EBP1, S6 and PKC-alpha, increased levels of cardiac hypertrophy markers, and a trend toward lower levels of myocardial autophagy. Hypercholesterolemia can now be added to the growing list of conditions associated with aberrant mTOR signaling. Hypercholesterolemia produces a unique profile of alterations in cardiac mTOR signaling, which is a potential target in cardiac diseases associated with hypercholesterolemia and nutritional excess.